Pengaruh Disiplin Kerja Dan Kompetensi Terhadap Kinerja Pegawai Pada Dinas Perpustakaan Dan Kearsipan Kota Tangerang Selatan - Muhamad Ilham Fadhil; Abu Bakar Dja far (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. This research aims to analyze the influence of work discipline and competence on employee performance at the Library and Archives Office of South Tangerang City. This study employed a quantitative method with an associative approach. The research sample consisted of 60 employees obtained through a saturated sampling technique. Data were collected through questionnaires, observation, and documentation, and then analyzed using instrument testing, classical assumption tests, multiple linear regression, correlation coefficient, coefficient of determination, as well as t-test and F-test with the assistance of SPSS version 26. The results show that: (1) Work discipline has a positive and significant effect on employee performance, with tcount > ttabel (13.800 > 2.002). This proves that the higher the employee’s discipline, the better the performance achieved. (2) Competence has a positive and significant effect on employee performance, with tcount > ttabel (17.552 > 2.002), which means that employees’ knowledge, skills, and work attitudes directly contribute to achieving performance targets. (3) Simultaneously, work discipline and competence have a positive and significant effect on employee performance, as indicated by Fcount > Ftabel (159.839 > 3.159) and significance level < 0.05. The multiple linear regression equation obtained is Y = -1.813 + 0.237 X1 + 0.786 X2, which shows that work discipline and competence positively affect employee performance. The coefficient of determination (R²) is 0.849 or 84.9%, while the remaining 15.1% is influenced by other factors not examined in this study, such as motivation, compensation, leadership, and work environment